Husband-Wife Relations in Polyandry Households: Empirical Study of Polyandry in Plosorejo Village, Kismantoro District Wonogiri - Yazid, Afthon; Diana Zuhroh; Na’im Jayus Romadlonna (Syakhsiyah Jurnal Hukum Keluarga Islam, 2025)
Abstract: This research discusses the practice of polyandrous marriage. The research location is in Pager Gunung Hamlet, which is part of Plosorejo Village, Kismantoro District, Wonogiri Regency, highlighting the factors behind the occurrence of polyandry and its legal implications.  Polyandry is a marriage system that is not permitted in Islamic law or positive law in Indonesia. This prohibition has been regulated in the Compilation of Islamic Law (KHI) and is contained in Law Number 1 of 1974 concerning Marriage. This research uses empirical methods with a qualitative approach, where data is obtained through interviews with polyandry practitioners, community figures, as well as analysis of related documents. The research results show that the main factors causing polyandry in this region are economic limitations, lack of understanding of religion, and social conditions that are permissive towards this practice. The case studied showed that a woman maintained relationships with two husbands for financial and health reasons, despite warnings from the local community. The legal implications of this practice include the unclear legal status of children born, the invalidity of marriages according to state law, and the negative impact on gender relations in the household. This research confirms that polyandry is contrary to religious and legal norms in Indonesia and has the potential to cause legal and social uncertainty. Therefore, an active role is needed from the village government and religious leaders in providing understanding to the community regarding marriage laws in order to prevent similar practices from occurring in the future. Keywords: Polyandry, marriage law, gender relations, legal implications, economic factors .